Aescin and diosmin each alone or in low dose- combination ameliorate liver damage induced by carbon tetrachloride in rats - Sara Mahmmoud EL-Dakhly; Abeer Abdallah Ali Salama; Soha Osama Mahmoud Hassanin; Noha Nazeeh Yassen; Alaaeldin Ahmed Hamza; Amr Amin (BMC Research Notes, 2020)
Abstract Objective This study evaluated hepatoprotective effect of aescin (AES) and diosmin (DIO), individually or in low-dose combination in chemically induced liver injury in rats. Rats were divided into 6 groups; Group 1, control, Group 2, injected with a single dose of a mixture of corn oil and carbon tetrachloride (CCl4) to induce hepatic toxicity. Before CCl4 injection, Groups 3–6 were treated daily for 14 days with silymarin (SIL) (200 mg/kg), aescin (AES; 3.6 & 1.75 mg/kg), Diosmin (DIO; 100 & 50 mg/kg). Serum samples were analyzed for different liver function, oxidative stress and antioxidant markers. Moreover, inflammation and tissue damage were confirmed by histological staining of liver tissue sections. Results Results indicated that CCl4 elevated serum levels of all assessed liver function markers and decreased levels of key antioxidants. Administration of AES and/or DIO significantly reversed all those CCl4-induced effects. Histopathological study showed disruption of the hepatic architecture, necrosis and inflammatory cells and depositions of glycogen and protein in the tissues of CCl4-treated group. Pretreatment with DIO and/or AES significantly improved histopathological structure of liver tissue. In conclusion, low-dose combination of AES and DIO exhibited significant and preferential hepatoprotective activity compared to individual treatment with AES or DIO.